Modelling the quality of life goals of people living with dementia. Issue 104 (February 2022) - Lockerbie, James; Maiden, Neil
Abstract: Although now well established, our information systems engineering theories and methods are applied only rarely in disciplines beyond systems development. This paper reports the application of the i* goal modelling language to describe the types of and relationships between quality of life goals of people living with dementia. Published social care frameworks to manage and improve the lives of people with dementia were reviewed to synthesize, for the first time, a comprehensive conceptual model of the types of goals of people living with dementia. This model was then refined in co-design workshops with experienced professional care workers. The conceptual model was used to construct automated reasoning capabilities in a new digital toolset that people with dementia can use for life planning. Highlights: Conceptual modelling of goals contributing to quality of life with dementia. Co-designing a model of quality of life with experienced care professionals. Automated reasoning about older people's daily goals and activities.